Pengaruh Service Quality Dan Sales Promotion Terhadap Impulse Buying Dalam Pembelian Secara Online Produk Bukalapak - Ilham Ramanto; Febsri Susanti (Jurnal Riset Ekonomi dan Akuntansi, 2023)
This study has a formulation of the problem How Tangible influences Impulse Buying in online purchases of Bukalapak products, How does Reliability affect Impulse Buying in online purchases of Bukalapak products, How does Responsiveness affect Impulse Buying in online purchases of Bukalapak products, How does Assurance affect Impulse Buying in online purchases of Bukalapak products, How does Empathy affect Impulse Buying in online purchases of Bukalapak products, How does Sales Promotion affect Impulse Buying in online purchases of Bukalapak products. This study aims to determine the effect of impulse buying in online purchases. This type of research is non-probability sampling. The sample consisted of 174 employees of the mdjamil pharmaceutical installation who shopped online at Bukalapak.